Isolated Celiac and Splenic Artery Dissection: A Case Report and Review of the Literature - Tania Moussa; Georges Nawfal; Tarek Assi; Elie El Rassy; Elie Massoud; Iskandar Daou (Case Reports in Vascular Medicine)
An isolated dissection of the celiac artery is an extremely rare condition that requires a high level of suspicion to evoke the diagnosis. Once established, the natural course is unpredictable in view of the discrepancies in its management requiring a case-by-case analysis. In this paper, we report an unusual case of spontaneous abdominal pain that was diagnosed with celiac and splenic artery rupture secondary to physical stress. This paper underlines the necessity to maintain a high level of suspicion for arterial dissections and we also review the management plan in such cases.